2021
DOI: 10.3171/2020.10.spine201307
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and swallowing outcomes in patients undergoing 4- and 5-level anterior cervical discectomy and fusion

Abstract: OBJECTIVE Anterior cervical discectomy and fusion (ACDF) is a common and robust procedure performed on the cervical spine. Literature on ACDF for 4 or more segments is sparse. Increasing the number of operative levels increases surgical complexity, tissue retraction, and risks of complications, particularly dysphagia. The overall risks of these complications and rates of dysphagia are not well studied for surgery on 4 or more segments. In this study, the authors evaluated their institution’s perioperative expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In fact, the largest study recently published on 4level and 5-level ACDF focuses on the complication and swallowing outcomes. 14 In addition, the small number of reports with varying results may not reflect the true nonunion rate because of the disparities in study methodologies, small patient cohorts, and .017 b C2-3 vs C3-4 vs C4-5 vs C5-6 vs C6-7 vs C7-T1, n (% of subsident level) 0 (0.0) vs 2 (16.7) vs 1 (8.3) different definitions of nonunion as echoed in the meta-analysis by Shriver et al 19 Therefore, this work seeks to provide a robust analysis of nonunion after 4 to 5-level ACDF by comparing the demographic and surgical differences between the nonunion and fusion groups. Both groups displayed comparable baseline characteristics except that significantly higher proportion of the nonunion patients presented with weakness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the largest study recently published on 4level and 5-level ACDF focuses on the complication and swallowing outcomes. 14 In addition, the small number of reports with varying results may not reflect the true nonunion rate because of the disparities in study methodologies, small patient cohorts, and .017 b C2-3 vs C3-4 vs C4-5 vs C5-6 vs C6-7 vs C7-T1, n (% of subsident level) 0 (0.0) vs 2 (16.7) vs 1 (8.3) different definitions of nonunion as echoed in the meta-analysis by Shriver et al 19 Therefore, this work seeks to provide a robust analysis of nonunion after 4 to 5-level ACDF by comparing the demographic and surgical differences between the nonunion and fusion groups. Both groups displayed comparable baseline characteristics except that significantly higher proportion of the nonunion patients presented with weakness.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The largest series on 4 to 5-level ACDF focused specifically on swallowing outcomes. 14 There are little data on nonunion rates in 4 to 5-level ACDFs. Therefore, this study analyzes factors predicting nonunion after 4 to 5-level ACDF by comparing patients who achieved fusion with those who failed to achieve fusion at 1 or multiple levels.…”
mentioning
confidence: 99%
“…didates for CDA. [45][46][47] Due to arthrodesis-related consequences, 22,39,[48][49][50][51] multilevel CDA is particularly appealing for young patients with multilevel cervical spondylotic myelopathy caused by disc-related problems or congenital stenosis. Chang et al 1 reported a retrospective series of 37 patients younger than 50 years with cervical myelopathy who were treated with either hybrid CDA-ACDF (2-level CDA plus 1-level ACDF, 20 patients) or 3-level ACDF (17 patients).…”
Section: Figmentioning
confidence: 99%
“…ACCF allows direct removal of the compression to the spinal cord and provides the cervical spine with a stable biomechanical environment via anterior arthrodesis at the operative levels. Although ACCF has been reported to exhibit good neurologic recovery [ 9 ], and restoration of cervical alignment in patients with CSM, the long-segment solid fusion inevitably sacrifices partial motor function of the cervical spine. The loss of motion at the operative levels can lead to an increased range of motion (ROM) of the adjacent intervertebral space [ 10 , 11 ], which can possibly lead to adjacent segment disease and resulting in CSM in those patients [ [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%